Mortgage choices and housing speculation - Gadi Barlevy; Jonas D. M. Fisher (Federal Reserve Bank of Chicago, 2010)
We describe a rational expectations model in which speculative bubbles in house prices can emerge. Within this model both speculators and their lenders use interest-only mortgages (IOs) rather than traditional mortgages when there is a bubble. Absent a bubble, there is no tendency for IOs to be used. These insights are used to assess the extent to which house prices in US cities were driven by speculative bubbles over the period 2000-2008. We find that IOs were used sparingly in cities where elastic housing supply precludes speculation from arising. In cities with inelastic supply, where speculation is possible, there was heavy use of IOs, but only in cities that had boom-bust cycles. Peak IO usage predicts rapid appreciations that cannot be explained by standard correlates and this variable is more robustly correlated with rapid appreciations than other mortgage characteristics, including sub-prime, securitization and leverage. Where IOs were popular, their use does not appear to have been a response to houses becoming more expensive. Indeed, their use anticipated future appreciation. Finally, consistent with the reason why lenders prefer IOs, these mortgages are more likely to be repaid earlier or foreclose. Combined with our model, this evidence suggests that speculative bubbles were an important factor driving prices in cities with boom-bust cycles.
Keywords: E0; O4; R0; 330; house prices; interest-only mortgages; subprime mortgages; securitization; speculation